Advances and Pitfalls of Specialized Pain Care through Public and Private Health Care Providers in Catalonia and the Balearic Islands: A Physician's Survey. (21st May 2022) - Medel, Javier; Serrano, Ancor; Batet, Carme; Lorente, Lluis; Bella, Susana; Ferrandiz, Marta; Monerris, María-del-Mar; Boada, Sergi; Villoria, Jesus; Ribera, Maria-Victoria; Montes, Antonio; Videla, Sebastian
Abstract : Optimal diagnosis and treatment of pain require a multidisciplinary approach that demands considerable coordination and forethought. A cross-sectional physician survey based on an online questionnaire was carried out to assess the adoption of multidisciplinary working patterns, compare the public and private models, and provide an update on the resources and organization of specialized pain care in Catalonia and the Balearic Islands. Active pain practitioners identified through the Catalan Health Service and Pain Society databases were sent an invitation in December 2020. Of the 321 physicians contacted, 91 (28.3%) answered and 71 provided complete responses (commonly anesthesiologists, representing 92 different sites; some worked at public and private sites). Up to 78.7% reported working in pain management teams, but only 53.5% were regularly involved in teaching or research activities. Thus, the proportion of multidisciplinary sites lies somewhere in-between. Median wait times were significantly shorter and within the recommended standards in private practices (e.g., 15 vs. 90 days in public practices for noncancer patients). In turn, private practices were slightly less staffed and equipped, albeit the differences did not reach statistical significance. Respondents made a median of 530 regular and 30 emergency visits per year, of which 190 involved interventional procedures. They offered a wide range of pharmacological and interventional therapies, although psychotherapy and the most sophisticated procedures were only available in ≤50% of sites. Pain clinicians and facilities are reasonably available in Catalonia, but barely more than half are truly multidisciplinary. Public and private practices differ in some aspects; the latter seems to be more accessible, but it is restricted to patients who can afford it. Compared to previous reports, this update shows both advances and outstanding issues. Multidisciplinary care could be expanded by incorporating more psychologists and some interventional procedures. The public practices should reduce wait times.